"Russiana gloriatur ecclesia" ir šv. Brunono Kverfurtiečio misijų klausimas - Ščavinskas, Marius (Lietuvos istorijos studijos, 2009)
The issue discussed in the article refers to the geography of the archdioceses, established by St. Bruno of Querfurt and the meaning and the circumstances of the appearance of the term "Russiana gloriatur ecclesia" mentioned "in the name of the Russian king" by the name Nethimer and the hagiographer Peter Damian (the first half of the 11th century). The greatest attention is focused on the letter to the king of Germany Henry II (the future emperor), written by St. Bruno himself and to the insert, written by Peter Damian, describing the martyrdom of St. Bruno Boniface's (1009).It becomes clear in the research that St. Bruno of Querfurt, after being anointed the archbishop of missions or pagans in 1004, did his work in at least several peripheries: in Hungary and in Kiev Russia, i.e., among "black Hungarians", Kiev Russia and Pechenegian, i.e., among Pechenegs. For the latter St. Bruno anointed the bishop and he also visited three Pechenegian lands. Another periphery, where people were sent by St. Bruno (the bishop and the monks), was Sweden. Finally the missionary himself came to Russian-Lithuanian border, where he was killed. All this geography shows, that St. Bruno of Querfurt did his missions and established the archdioceses in particular peripheries, in territories not available for any political influences, where other bishops were not doing their work and which didn't lie within other bishops' jurisdiction.With the view of avoiding the violation of political and church subordination law in relationship to other bishops and the rulers, supporting them, St. Bruno, if we trust hagiographical sources, visited Prussia, but he didn't do any missions there—instead he immediately headed for the Russian-Lithuanian border. While considering that we can answer the question why there is a mention of "Russiana gloriatur ecclesia" in Peter Damian's hagiography. The hagiographer perhaps has in mind the archdiocese, established by St. Bruno, the core of which was Kiev Russia. Because the bordering lands, where St. Bruno and the people sent by him worked, were on the border with Kiev Russia. Since the first archbishop of this missionary archdiocese was St. Bruno himself "Russian Church" took pride in him, i.e. the former and the present disciples of St. Bruno. Thus, while mentioning Russiana gloriatur ecclesia Peter Damian might have had in mind the people who still remembered St. Bruno, his disciples, the congregation of Russian Latin Church.Rex russorum, mentioned in the same hagiography, might have meant not the "Russian" king, who lived in Lithuania, and who allegedly belonged to the sphere of Kiev Russian geopolitical influence, but the leader of the tribe, who lived in Lithuania, turned into such "king" due to a more familiar name of Russia.Since St. Bruno of Querfurt did his missions in different peripheries, related to Kiev Russia, the Russian-Lithuanian border, the subject of our concern, should be closer to Kiev Russia. This should be taken into consideration while dealing with the issue of Russia's mention in the sources. Therefore it is possible to agree with the argument, stated by D. Baron, that Peter Damian hadn't confused us with Russians, but the conclusion made by E. Gudavičius, that all sources, speaking about the land of the "Russian king" speak about one and the same geographical area.